2019
DOI: 10.1161/strokeaha.118.023972
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and Molecular Features of 5 European Multigenerational Families With Moyamoya Angiopathy

Abstract: Background and Purpose Moyamoya angiopathy (MMA) is a rare cerebral vasculopathy outside of Asia. In Japanese patients, a vast majority of patients carry the founder p.R4810K variant in the RNF213 gene, and familial cases are around 10%. In European patients, data about familial occurrence are limited. The aim of this study was to characterize the clinical and molecular features of several European families with a parent-to-child transmission of MMA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…3) [38]. It has a higher incidence in Japan and Korea, probably due to founder mutations [39][40][41][42]. Histopathological studies have shown that pathophysiological pathways of European and Asian MA seem identical despite different genetic predispositions [43].…”
Section: Moyamoya Angiopathymentioning
confidence: 99%
“…3) [38]. It has a higher incidence in Japan and Korea, probably due to founder mutations [39][40][41][42]. Histopathological studies have shown that pathophysiological pathways of European and Asian MA seem identical despite different genetic predispositions [43].…”
Section: Moyamoya Angiopathymentioning
confidence: 99%
“…Importantly, PALD1 has been genetically associated with Moyamoya disease in two families. Moyamoya disease is caused by the occlusion of the carotid artery and its branches, causing characteristic pronounced collateral vessel formation and stroke in the central nervous system (Grangeon et al , 2019). A potential causal link between the hyperactive endothelial signalling observed in the Pald1 −/− mouse and excessive collateral formation in patients with Moyamoya disease need further investigations.…”
Section: Resultsmentioning
confidence: 99%
“…18 For instance, variants of RNF213 account for the genetic susceptibility of Asian patients, with approximately 80% with moyamoya harboring the heterozygous p.R4810K founder variant. 19 RNF213 has been shown in vivo and in vitro to play a significant role in controlling angiogenesis through regulating the expression of matrix metalloproteinases in endothelial cells. 20 We now expand the spectrum of genetic arteriopathies to include CBL-mediated arteriopathy.…”
Section: Discussionmentioning
confidence: 99%